The Treatment Effects of Sliding Mechanic System During En-Masse Retraction in Adult Maxillary Dental Protrusion Patients - Aweekhun Thanasansomboon (Prince of Songkla University, 2018)
Thesis (M.Sc., Oral Health Sciences)--Prince of Songkla University, 2017